Registered report evidence suggests no relationship between objectively-tracked video game playtime and wellbeing over 3 months - Ballou,N; Sewall,CJR; Ratcliffe,J; Zendle,D; Tokarchuk,L; Deterding,S (Technology, Mind, and Behavior, 2024)
Recent years have seen intense research, media and policy debate on whether amount of time spent playing video games (“playtime”) affects players’ wellbeing. Existing research has used cross-sectional designs with easy-to-obtain but unreliable self-report measures of playtime, or, in rare instances, obtained industry data on objectively-tracked playtime but only for individual games, not a player’s total playtime across games. Further, researchers have raised concerns that publication bias and a lack of differentiation between exploratory and confirmatory research have undermined the credibility of the evidence base. As a result, we still do not know whether wellbeing affects playtime, playtime affects wellbeing, both, or neither. To track people’s playtime across multiple games, we developed a method to log playtime on the Xbox platform. In a 12-week, 6-wave panel study of adult US/UK Xbox-predominant players (414 players, 2036 completed surveys), we investigated within-person temporal relations between objectively-measured playtime and wellbeing. Across multiple preregistered model specifications, we found that the within-person prospective relationships between playtime and wellbeing, or vice versa, were not practically significant—even the largest associations were unlikely to register a perceptible impact on a player’s wellbeing. These results support the growing body of evidence that playtime is not the primary factor in the relationship between gaming and mental health for the majority of players, and that research focus should be on the context and quality of gameplay instead.